Aktualisasi Dakwah Transformatif di Masa Pandemi Covid-19 - Mochammad Irfan Achfandhy (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2020)
The problem of violating the Covid-19 health protocol in religious activities which is the cause of the emergence of new clusters of the spread of the virus cannot be separated from the role of Islamic Religious Counselors. Da'wah as the main task of Islamic Religious Extension is very important in fostering society and shaping social transformation in the form of changing habit patterns according to the Covid-19 protocol. This service activity aims to elaborate on the actualization of da'wah carried out by Islamic Religious Counselors in campaigning for the Covid-19 health protocol and forming social transformation. This activity was carried out in 2022 and was attended by Islamic Religious Counselors, Kalasan District, Sleman Regency. Then, to evaluate the effectiveness of the activity, in-depth interviews and field observations were carried out on the da'wah activities of Islamic Religious Counselors, Kalasan District, Sleman Regency during the Covid-19 pandemic. The results of this activity indicate that the da'wah messages of Islamic Religious Counselors are oriented towards social values, advocating for affected communities, choosing interactive dialogue communication strategies, building stakeholders with related parties as an effort to empower communities affected by Covid-19. The contribution of this activity is that the overall actualization of the da'wah of Islamic Religious Counselors during the Covid-19 pandemic is effective if it is carried out with an assistance model to realize social transformation, especially in religious activities.